2011 IEEE 5th International Conference on Cybernetics and Intelligent Systems (CIS) 2011
DOI: 10.1109/iccis.2011.6070338
|View full text |Cite
|
Sign up to set email alerts
|

Face detection using neural networks with skin segmentation

Abstract: Detecting faces in images remains a challenge in image processing and is currently an active area of research. A frontal face detection algorithm is presented in this paper. Skin colors were used to initially detect possible faces in the image. Using a search window, possible faces are processed using edge detection. These are then classified as faces or non faces using an artificial neural network classifier. The algorithm was tested in images with varying sizes and number of faces. Results from experiments d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 15 publications
0
13
0
Order By: Relevance
“…This article identifier additionally proficiently recognizes the nose, body, eyes etc. This paper examines about the different element vectors that can be utilized to distinguish a face utilizing the algorithm [4]. The face recognition is constrained by the course object discovery system.…”
Section: Algorithm Implementationmentioning
confidence: 99%
“…This article identifier additionally proficiently recognizes the nose, body, eyes etc. This paper examines about the different element vectors that can be utilized to distinguish a face utilizing the algorithm [4]. The face recognition is constrained by the course object discovery system.…”
Section: Algorithm Implementationmentioning
confidence: 99%
“…In this study, the 16 input variables shown in Table 1 is presented in binary and equivalent to 2 16 − 1 or 65,535 combinations. For a given sample, the HFNN model may take in the values of 2 input variables, e.g., Age and Total Income, and ignoring the values of the remaining 14 input variables.…”
Section: Pruning the Input Variables Or Fuzzy Setsmentioning
confidence: 99%
“…Neural Network (NN) is an information processing paradigm that is inspired by the way biological nervous systems, such as the brain, process information [14][15][16]. The key element of this paradigm is the novel structure of the information processing system.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Artificial neural networks are computational models that mimics the human brain, with various interdisciplinary applications, e.g. agriculture/aquaculture [4][5] [6] [7], healthcare [8][9] [10], face detection [11], voice recognition [12], electronic communication [13], forensics [14], etc. In this study, deep artificial neural network was applied for mango detection and quality & ripeness classification tasks in an embedded system environment.…”
mentioning
confidence: 99%